A study of crime potentials and physical design in Taman Melati terrace housing area of Kuala Lumpur City - Mohit, Mohammad Abdul (Research Management Centre, IIUM, Kuala Lumpur, 2011)

(untitled)
Recently, Malaysia has adopted the “Safe city programme” launched by the Ministry of Housing and Local Government, with the cooperation of the Federal Department of Town and Country Planning (2005), which is focused towards achieving four objectives, the most important of which is creating cities free from violence and crime. So far studies have identified that changes in the built environment and modifications to the space design can affect both residents and offenders perceptions of criminality. Various place-based crime prevention techniques are employed to create a place that is easy to defend. The main aim of the research is to examine the effectiveness of these techniques in providing a safe environment in two housing areas - terrace housing along main road (AMR) and terrace housing around the open space (AOS), in Taman Melati of Kuala Lumpur City. To achieve the objectives and answer the research questions, a triangulation approach was used in which data was gathered by applying both quantitative (questionnaire and observation) and qualitative (interview) methods. The findings showed that the crime risk was higher in the AOS terrace houses than in the AMR terrace units. All the factors showed correlations with the safety level except for omni-presence. It was also found that most of the break-ins were through the front door and that the most frequent crime is street snatching. Based on the research finding, the study draws several recommendations which include enhancement of the natural surveillance, installing higher perimeter fencing, provision of adequate lighting for pedestrian walkways and educational and awareness programmes for the residents.